Occurrence of southern right whales (Eubalaena australis) along southeastern Brazil - de Oliveira Santo, Marcos César; Siciliano, Salvatore; Pacheco de Souza, Shirley; Altmayer Pizzorno, Jose Luis (J. Cetacean Res. Manage., 2020)
This paper reports on the occurrence of southern right whales (Eubalaena australis) in southeastern Brazilian waters (18°S-25°S), with evidence of their use of the region as an important calving area. Only in recent years have right whale sightings and strandings been reported regularly within the surveyed area. Of 71 distinct sightings reported since 1936, 39 (54.9%) were mother-calf pairs observed close to the shore. Most of these sightings (91.5%) were reported from early July to late October. Eight confirmed strandings of this species were observed within the surveyed area, six of which were between July and October. Stranded calves represented 62.5% of these records. Two calves showed evidence of incidental capture. The increasing number of sightings, and recent reports of stranded calves and one adult female could be indicative of an increase in cetacean research efforts in the region. However, it also suggests use of the southeastern Brazilian coast as an important right whale calving area.